Digital literacy and the attitude of educators towards MOOC platform in GCC countries - AlQaidoom, Hana (IEEE, 2019)
This study is pursued to identify the digital literacy level required to implement Massive Open Online Course (MOOC) by educators in higher education institutions (HEIs) of Gulf Cooperation Council (GCC) countries. It is also intended to determine the attitude of educators in GCC towards the adoption of MOOC as a prospective e-learning initiative in education. In the light of that, proposing a unified GCC MOOC platform based on the information obtained is also considered as one of the main aspects to carry out as part of this study. MOOC is adopted by few higher education institutions in the Gulf countries; however, very little researches have been conducted to highlight the importance of digital literacy on educators' attitude towards educational technologies initiatives in GCC countries. There are also rare studies that cover the attitude of educators towards the adoption of MOOC in GCC. Most of the studies focus on the perception and attitude of learners and users but not the educators. This study will utilize “Digital Literacy Scale” (DLS) to measure the level of digital literacy of educators. While “Unified Theory of Acceptance and Use of Technology” (UTAUT) model is adapted to identify the attitude of educators towards MOOC as an e-learning platform. Consequently, this will lead to proposing a unified MOOC for GCC countries. Questionnaires will be administered on a sample of educators from universities and colleges in GCC countries that apply MOOC. In addition, observations and focus group interviews will be implemented to answer the questions of this study.